AN ETHNOGRAPHY STUDY ON LANGUAGE SHIFT OF MIGRANT FAMILIES - Eni Dwi Lestari (Universitas Islam Lamongan, 2016)
The objectives of this research are to describe the process and the factors of language shift in the migrants at Sugihwaras Village, Deket Subdistrict, Lamongan Regency. This ethnography research explores the observable and learned patterns of behavior, customs, and ways of life of a culture-sharing group. The writer emphasizes on the language shift as the part of culture. In this research, the writer presents the data by describing and analyzing the data based on the language shift as the social phenomenon and it also studied from the point of view of Sociolingustics studyThe subject of this research is two migrant families, who stay in Sugiwaras Village, Deket Subdistrict, Lamongan Regency. The first family is Madurese, and the second is Bugisnese. The research found that the process of language shift in the migrant at Sugihwaras Deket Lamongan occurs gradually. The migrant use Indonesia as their bridge to communicate with the society previously.Keywords: language shift, migrant family